A national assessment of elective cesarean sections in Bangladesh and the need for health literacy and accessibility - Awan Afiaz (Nature Portfolio, 2021)
Abstract There has been a gradual rise in the number of cesarean sections (CSs) in Bangladesh. The present study identified the cohort of women, who were more likely to opt for an elective CS based on their sociodemographic characteristics, pre-delivery care history, and media exposure, using the Bangladesh Multiple Indicator Cluster Survey-2019. The survey stratification adjusted logistic regression model and interpretable machine learning method of building classification trees were utilized to analyze a sample of 9202 women, alongside district-wise heat maps. One-in-five births (20%) were elective CSs in the 2 years prior to the survey. Women residing in affluent households with educated house-heads, who accessed antenatal care prior to delivery (AOR 4.12; 95% CI 3.06, 5.54) with regular access to media (AOR 1.31; 95% CI 1.10, 1.56) and who owned a mobile phone (AOR 1.25; 95% CI 1.04, 1.50) were more likely to opt for elective CSs, which suggests that health access and health literacy were crucial factors in women’s mode of delivery. Spatial analyses revealed that women living in larger cities had more elective CS deliveries, pointing towards the availability of better health and access to multiple safe delivery options in peripheral areas.